Adsorption of NH4+-N on Chinese loess: Non-equilibrium and equilibrium investigations. (1st November 2017) - Xie, Haijian; Wang, Shaoyi; Qiu, Zhanhong; Jiang, Jianqun
Abstract: NH4 + -N is a crucial pollutant in landfill leachate and can be in high concentrations for a long period of time due to anaerobic condition of landfills. The adsorption properties of NH4 + -N on the Chinese loess were investigated using Batch test. The influences of ammonium concentration, temperature, reaction time, slurry concentration, and pH on the adsorption process are evaluated. Adsorption kinetics and isotherm behaviors were studied by applying different models to the test data to determine the adsorption parameters. The equilibrating duration was shown to be less than 60 min. The data on adsorption kinetics can be well fitted by the pseudo-second-order kinetics model. According to the Langmuir isotherm model, the adsorption capacity of Chinese loess about NH4 + -N was predicted to be 72.30 mg g −1 . The uptake of NH4 + -N by Chinese loess was considered to be the type of physical adsorption on the basis of D–R isotherm analysis. The optimal pH and slurry concentration are 4 and 2 g/50 ml, respectively. According to the calculated values of free energy, enthalpy and entropy change, the adsorption process is determined to be exothermic. The disorder of the system appeared lowest at temperature of 308.15 K. The predicted Gibb's free energies also indicate the adsorption process is endothermic and spontaneous. The FTIR spectrum and EDX analysis showed the adsorption process of NH4 + involves cation exchange and dissolution of calcite. Graphical abstract: Highlights: Adsorption properties of NH4 + -N on Chinese loess were investigated using Batch test. Equilibrating time for ammonium adsorption on loess was less than 80 min. Adsorption capacity of Chinese loess about ammonium was 72.30 mg g −1 . Ammonium adsorption is a physical adsorption according to D–R isotherm analysis.